Numerical simulation of the May 15 and April 26, 1991 tornadic thunderstorms - Grasso, Lewis Donald, author (Colorado State University. Libraries, 1996)
Two tornado simulations were performed for this study. The first was for May 15, 1991. On this day a strong F2/F3 tornado struck Laverne, Oklahoma. The second was for April 26, 1991. A violent F4/F5 moved across north central Oklahoma. Both tornadic storms were triggered by a dry line. The RAMS mesoscale model was initialized with standard synoptic scale data. The soil moisture was initialized with station precipitation reports. A total of six grids were used in both case:,. The model was able to generate a dry line in both cases. Deep tropospheric convection formed along the dry lines in the third grid. This grid had a horizontal grid spacing of 5.0km. No cumulus parameterization, warm bubbles or any other numerical technique was used to aid the development of convection. A supercell thunderstorm formed approximately one hour after convection was initiated in both cases. As the storms moved towards the northeast an eastward bulge formed in the dry line. Cyclonic rotation began at the nose of the bulge in the lower boundary layer, beneath the convective storms. While the storms moved away from the dry line the forward flanking precipitation downdrafts expanded. Horizontal vorticity was positively tilted in the southern side of the downdrafts. The resulting vertical vorticity was horizontally converged to feed the intensifying tornadoes. In time the downdrafts wrapped around to the rear flanks of the storms causing vertical vorticity to be produced in a larger area. The tornadoes were mature at this time. Both tornadoes formed within the boundary layer and moved upward into the parent thunderstorm. At the mature stage, both tornadoes reached the storms' top. The origin of rotation was vertical vorticity generated by positive tilting of horizontal vorticity in the lowest few hundred meters in the downdrafts. The maximum horizontal wind speed for the May case was 60m/s at 50m. The pressure drop in the core was 30mb. The April tornado had a maximum horizontal wind speed of 102m/s at 50m with a pressure drop of 95mb in the core.
Numerical simulation of the May 15 and April 26, 1991 thunderstorms
January 25, 1996.
Keywords: Thunderstorms; Numerical weather forecasting